An analysis of suspicious transaction reporting decisions in Malaysia’s money services business - Jamil, Azzril bin; Johari, Razana Juhaida; Zarefar, Arumega; Yudi, Melissa Mam (Edelweiss Applied Science and Technology, 2024)
Bank Negara Malaysia has imposed the requirement to report suspicious transactions to all financial institutions in Malaysia, including money services businesses. The requirement was codified in the Anti-Money Laundering, Anti-Terrorism Financing, and Proceeds of Unlawful Activities Act 2001, and failure to comply with the requirement can amount to a severe financial penalty. However, a few reported cases against the money services business due to failure to report suspicious transactions had shaken the public’s confidence and had a huge adverse impact on the credibility and integrity of the money services business. This study is conducted to examine the factors that could influence suspicious transaction reporting, namely knowledge, training, and customer due diligence. The Statistical Package for Social Science (SPSS) version 25 software was used for analysis of the data, which were collected by sending questionnaires to 163 money laundering reporting officers currently working with money services businesses in Malaysia. The results revealed that knowledge and training had a significant positive effect on suspicious transaction reporting decisions, but not customer due diligence. The results from this study could be used by the trade association and Bank Negara Malaysia in developing an evocative competency development program for money laundering reporting officers in Malaysia. These findings would also benefit money laundering reporting officers, money services businesses, and academia. Limitations and recommendations for future research are discussed.